Ethylene signaling is important for isoflavonoid-mediated resistance to rhizoctonia solani in roots of medicago truncatula - Liu, Y.; Hassan, S.; Kidd, B.; Garg, G.; Mathesius, U.; Singh, Karam; Anderson, J. (American Phytopathological Society, 2017)
© 2017 The American Phytopathological Society The root-infecting necrotrophic fungal pathogen Rhizocto-niasolani causes significant disease to all the world’s major food crops. As a model for pathogenesis of legumes, we have examined the interaction of R. solani AG8 with Medicago truncatula. RNAseq analysis of the moderately resistant M. truncatula accession A17 and highly susceptible sickle (skl) mutant (defective in ethylene sensing) identified major early transcriptional reprogramming in A17. Responses specific to A17 included components of ethylene signaling, reactive oxygen species metabolism, and consistent upregulation of the isoflavonoid biosynthesis pathway. Mass spectrometry revealed accumulation of the isoflavonoid-related compounds liquiritigenin, formononetin, medicarpin, and biochanin A in A17. Overexpression of an isoflavone synthase in M. truncatula roots increased isoflavonoid accumulation and resistance to R. solani. Addition of exogenous medicarpin suggested this phytoalexin may be one of several isoflavonoids required to contribute to resistance to R. solani. Together, these results provide evidence for the role of ethylene-mediated accumulation of isoflavonoids during defense against root pathogens in legumes. The involvement of ethylene signaling and isoflavonoids in the regulation of both symbiont-legume and pathogen-legume interactions in the same tissue may suggest tight regulation of these responses are required in the root tissue.